Free movement of persons within the European Community - Weiss, Friedl (Kluwer Law International The HagueNL, 2002)
Presents an overview of European Community law relating to the free movement of persons. Considers briefly, matters concerning companies such as their freedom of establishment. Deals with diverse subjects viz. visas, the free movement of workers, posted workers, the harmonization of professional qualifications, freedom to provide and receive services, European citizenship and agreements between the European Community and other states concerning free movement.